STUDY OF ND: YAG LASER ENERGY LEVELS REQUIRED FOR DIFFERENT TYPES OF POSTERIOR CAPSULE OPACIFICATION - Sushant Durkar, Vibhavari Barhate , Yogendra Vabale, Smita Pawar ,Saurabh Shinde, Karina Dalwai, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
To assess the average Nd:YAG laser energy required for various morphological forms ofposterior capsule opacification (PCO) and to evaluate post-laser changes in best-corrected visual acuity (BCVA) and intraocular pressure (IOP).